Nurses knowledge and practice towards prevention on deep vein thrombosis in University of Gondar Comprehensive Specialized Hospital, northwest Ethiopia - Nurhusien Nuru Yesuf; Tadesse Abebe; Ruth Adane; Rahel Lelisa; Mihret Asefa; Marta Tessema; Yeneabat Birhanu (Elsevier, 2021)
Introduction: Deep vein thrombosis is a common problem among people who are immobile for a long period of time. Although it is preventable, it is still one of the problems of the people related to poor knowledge and practice of nurses on Deep Vein Thrombosis prevention. There is no study conducted regarding the magnitude of occurrence of Deep Vein Thrombosis among nurses in the study area. Thus it needs to assess the knowledge and awareness of nurses on Deep Vein Thrombosis prevention to avoid complications. Objectives: This study is aimed to assess Nurses Knowledge and Practice towards the prevention of Deep Vein Thrombosis at the University of Gondar Comprehensive Specialized Hospital, North West Ethiopia. Method: A cross-sectional study was conducted on the nurses who were working at the University of Gondar Comprehensive Specialized Hospital. A self-administered structured questionnaire was used to collect data. The data were entered into EPI- INFO version 7 then exported into SPSS version 20 statistical package for analysis. Finally, the summary statistic was used to describe the study population. Results: Out of the 422 staff nurses, 400 participants agreed to participate in the study with a response rate of 94.78 %. Of these, 60.5 % of the respondents and 39.5% had good and poor knowledge of Deep Vein Thrombosis respectively. About 78.9% of nurses had poor knowledge of Deep Vein Thrombosis prevention. Regarding to the practice, 42.5% of nurses had a good practice and 57.5% of nurses had poor practice, 39.4%, and 60.6% had good and poor practice towards prevention respectively. Conclusion and recommendation: More than half of the nurses were found to have inadequate knowledge and poor practice about deep vein thrombosis prevention. In order to enhance the knowledge and practice of the nurses of deep vein thrombosis; implementation of the comprehensive, systematic, and continuous educational program were recommended.